Managing the right ventricular outflow tract for pulmonary regurgitation after tetralogy of Fallot repair. Issue 1 (25th June 2013) - Hauser, Michael; Eicken, Andreas; Kuehn, Andreas; Hess, John; Fratz, Sohrab; Ewert, Peter; Kaemmerer, Harald
Abstract : The long-term outcome of patients with tetralogy of Fallot (TOF) with reconstruction of the right ventricular (RV) outflow tract is often complicated by the sequelae of severe pulmonary regurgitation. Progressive enlargement of the right ventricle, biventricular dysfunction and arrhythmia are apparent in more than 50% of the patients in the fourth decade of life. Pathophysiologic implications, clinical assessment and diagnostic modalities are discussed, whereas CMR imaging seems to be the procedure of choice. Therapeutical options for rereconstruction of the RV outflow tract are mentioned, surgical and interventional procedures are explained in detail. The optimal timing of reoperation for significant pulmonary regurgitation after TOF repair is still a matter of controversy given the limited runtime of the lately implanted prostheses and the risk of further reoperation. Early surgery is recommended in these patients before symptoms develop, or RV function has declined. Today we believe that waiting for the patient to become symptomatic is too late. All in all, pulmonary valve replacement is at least indicated in patients developing symptoms due to severe pulmonary regurgitation, particularly if associated with substantial or progressive RV dilatation, tricuspid regurgitation and/or supraventricular or ventricular arrhythmias.